ANALISA PENGARUH BRAND REJUVENATIONTERHADAP PEMBENTUKAN PURCHASE INTENTION DENGAN BRAND IMAGESEBAGAI VARIABEL INTERVENING PADA TEPUNG PREMIKS CHESA BOX PT. ISM BOGASARI FLOUR MILLS - Juliana Juliana; Diah Dharmayanti (Jurnal Manajemen Pemasaran, 2015)
Chesa Box Premix Flour is a product of consumer goods produced by PT. ISM Bogasari Flour Mills. In 2002, Chesa Box Premix Flour has been produced and sold in bulk, but in 2004 had to be discontinued because of the internal reason on the company. After more than ten years, in 2014 Chesa Box Premix Flour re-introduced to the market using the brand rejuvenation strategy. This research aims to analyze the relationship between brand rejuvenation, product innovation, and repositioning towards the formation of purchase intention on Chesa Box Premix Flour by using its brand image as an intervening variable. This causal research using questionnaires as a method and will be distributed to 110 respondents which is a sample of this research. The results showed that all of the variables involved in this study each have a significant impact as evidenced by the method of hypothesis testing t-test or reject the rejection of H0 if [T-stats] > T table that is equal to 1.96.